PERANGKAP TIKUS OTOMATIS MENGGUNAKAN SENSOR PASSIVE INFRARED (PIR) BERBASIS MIKROKONTROLER ATMEGA16 - Elly Mufida; Miftahul Fikri (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2015)
Rat is one of the pests is quite disturbing, especially in warehouses to store food or items that are favored by the mice. Automatic rat trap is designed so that it can be used to catch mice with more than one rat. This tool uses a Passive Infrared Sensor (PIR) to detect the presence of rats. An automation tool is controlled by a microcontroller Atmega 16, which receives inputs from sensors Passive Infrared (PIR). Based on input from the PIR sensor, then the microcontroller will move the entrance to the trap through the DC motor. The design of the tool is expected to be one of the solutions to reduce the rat population that is in the food storage warehouse or other goods. From the results of the experiment, mice trap that the tool is very effective for catching rats with the number more than one, depending on the area reservoir trap.